High Performance Supercapacitor Electrodes from Electrospun Nickel Oxide Nanowires - Rajan, Jose; Baiju, Vidyadharan; Izan Izwan, Misnon; Radhiyah, Abd Aziz; Jamil, Ismail; M. M., Yusoff; Nurul Khairiyyah, Mohd Zain (Elsevier Ltd, 2014)
Electrochemical energy storage using pseudocapacitive mode is under intense research owing to their potential in fabricating high performance renewable energy devices at a lower cost. In this paper we characterize nickel oxide (NiO) nanowires developed by electrospinning an aqueous polymeric solution containing nickel precursor for its application as a pseudocapacitors electrode. The wires are of diameter ~50 – 70 nm containing densely packed cuboidal grains (~10 – 20 nm) with less degree of crystal defects. Electrochemical properties of the electrodes fabricated on a nickel foam substrates are evaluated by cyclic voltammetry (CV) and charge – discharge cycling (CDC), and electrochemical impedance spectroscopy (EIS) techniques. The best performing devices showed a specific capacitance (CS) of ~ 670 Fg-1 with high cycling stability (~100%) for over 1000 cycles and Coulombic efficiency ~98%. Lower electrochemical equivalent resistance (~0.76 ), charge transfer resistance (~0.45 ), and charge relaxation time (43 ms) are observed which are attributed to the defect free nanowire morphology that give rise to the superior performance.